Impact of Immunosuppressive Agents on Clinical Manifestations and Outcome of Staphylococcus aureus Bloodstream Infection: A Propensity Score–Matched Analysis in 2 Large, Prospectively Evaluated Cohorts. (29th April 2021) - Camp, Johannes; Glaubitz, Lina; Filla, Tim; Kaasch, Achim J; Fuchs, Frieder; Scarborough, Matt; Kim, Hong Bin; Tilley, Robert; Liao, Chun-Hsing; Edgeworth, Jonathan; Nsutebu, Emmanuel; López-Cortés, Luis Eduardo; et al.
Abstract: Background: Staphylococcus aureus bloodstream infection (SAB) is a common, life-threatening infection. The impact of immunosuppressive agents on the outcome of patients with SAB is incompletely understood. Methods: Data from 2 large prospective, international, multicenter cohort studies (Invasive Staphylococcus aureus Infections Cohort [INSTINCT] and International Staphylococcus aureus Collaboration [ISAC]) between 2006 and 2015 were analyzed. Patients receiving immunosuppressive agents were identified and a 1:1 propensity score–matched analysis was performed to adjust for baseline characteristics of patients. Overall survival and time to SAB-related late complications (SAB relapse, infective endocarditis, osteomyelitis, or other deep-seated manifestations) were analyzed by Cox regression and competing risk analyses, respectively. This approach was then repeated for specific immunosuppressive agents (corticosteroid monotherapy and immunosuppressive agents other than steroids [IMOTS]). Results: Of 3188 analyzed patients, 309 were receiving immunosuppressive treatment according to our definitions and were matched to 309 nonimmunosuppressed patients. After propensity score matching, baseline characteristics were well balanced. In the Cox regression analysis, we observed no significant difference in survival between the 2 groups (death during follow-up: 105/309 [33.9%] immunosuppressed vs 94/309 [30.4%] nonimmunosuppressed; hazard ratio [HR], 1.20 [95% confidence interval CI, .84–1.71]). Competing risk analysis showed a cause-specific HR of 1.81 (95% CI, .85–3.87) for SAB-related late complications in patients receiving immunosuppressive agents. The cause-specific HR was higher in patients taking IMOTS (3.69 [95% CI, 1.41–9.68]). Conclusions: Immunosuppressive agents were not associated with an overall higher mortality. The risk for SAB-related late complications in patients receiving specific immunosuppressive agents such as IMOTS warrants further investigations. Abstract : Immunosuppressive medication was not associated with significantly higher mortality in Staphylococcus aureus bacteremia (SAB) in data from 2 international, multicenter cohorts. SAB-related late complications, however, were more frequent in patients taking immunosuppressive agents other than steroids.